Letter to the Editor concerning the article “Clinical outcomes of chondroblastoma treated using synthetic bone substitute: risk factors for developing radiographic joint degeneration” - Bo-Wen Zheng; Bo-Yv Zheng; Hua-Qing Niu; Xiao-Bin Wang; Jing Li (World Journal of Surgical Oncology, 2021)
Abstract The purpose of this letter to the Editor is to report some shortcomings in the statistical analysis and variable grouping in the recent publication of the article “Clinical outcomes of chondroblastoma treated using synthetic bone substitute: risk factors for developing radiographic joint degeneration,” and to further explore some of the factors that may affect the clinical prognosis of chondroblastoma patients. We also suggest future prospective controlled studies with large samples to improve the limitations encountered by Outani et al. (World J Surg Oncol. 18(1):47, 2020) due to insufficient statistical power of variables and lack of controls.